1999
DOI: 10.1159/000014577
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin in Epilepsy: First Results of Replacement Therapy and First Clinical Results

Abstract: At a single evening dose of 5–10 mg, melatonin (MLT), the pineal gland hormone, can exert a positive effect on the frequency of epileptic attacks in children with sleep disturbances of various etiologies. We have shown that the sleep behavior can be normalized and an existing epilepsy can be favorably influenced. Pretherapeutic MLT secretion profiles can provide new information concerning the origin and treatment of these disturbances. In vitro experiments suggest that this effect might be the result of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(55 citation statements)
references
References 16 publications
1
53
0
1
Order By: Relevance
“…The anti-excitatory effects of melatonin are probably secondary to its antioxidant effect [5]. When it is administered in pharmacological doses in children, it leads to reduction in severity and frequency of epileptiform activity [6]. It shows an effect contrary to glutamate, which is an excitatory neurotransmitter, i.e.…”
Section: öZmentioning
confidence: 99%
“…The anti-excitatory effects of melatonin are probably secondary to its antioxidant effect [5]. When it is administered in pharmacological doses in children, it leads to reduction in severity and frequency of epileptiform activity [6]. It shows an effect contrary to glutamate, which is an excitatory neurotransmitter, i.e.…”
Section: öZmentioning
confidence: 99%
“…Seizure is one of the primary causes of oxidative stress that induced neuronal cell death. Recently, melatonin is discussed in relation to epileptic seizure [100][101][102]. Melatonin has been known for antioxidant as a free radical scavenger.…”
Section: Neuroprotective Effect Of Melatonin On Seizures In Autistic Fxsmentioning
confidence: 99%
“…Furthermore, studies have reported that the primary beneficial effect of melatonin on seizure activity is due to its ability to synchronize disturbed circadian rhythms in epileptic patients (Fauteck et al, 1999;Peled et al, 2001). Comorbidity of a sleep disorder with epilepsy creates difficulties in choosing an anti-epileptic drug (AED).…”
Section: Melatonin and Epilepsymentioning
confidence: 99%
“…In line with this, melatonin and melatonin receptor agonists may be suitable for use as add-on treatments with routine AEDs. Indeed, melatonin alleviates sleep disturbances of different etiologies in epileptic children and adults (Coppola et al, 2004;Fauteck et al, 1999;Peled et al, 2001). …”
Section: Melatonin and Epilepsymentioning
confidence: 99%